Nitrogen and Phosphorus Co-doped Porous Carbon for High-Performance Supercapacitors - Zhou, Jiaming; Ye, Shewen; Zeng, Qinqin; Yang, Hui; Chen, Jiahao; Guo, Ziting; Jiang, Honghui; Rajan, Karthikeyan (Frontiers in Chemistry, 2020)
As one of the most promising fast energy storage devices, supercapacitor has been attracting intense attention for many emerging applications. However, how to enhance the electrochemical performance of electrode materials is still the main issue among various researches. In this paper, hierarchical porous carbon derived from Eleocharis dulcis has been prepared by chemical activation process with the aid of KOH at elevated temperature. Results show that the N, P co-doped porous carbon exhibits excellent electrochemical performance, it owns a specific capacitance of 340.2 F/g at 1 A/g and obtains outstanding cycling stability of 96.9% of capacitance retention at 10 A/g after 5000 cycles in a three-electrode system. Moreover, in the two-electrode system, the product still maintains a high specific capacitance of 227.2 F/g at 1 A/g, and achieves good electrochemical cycle stability (94.2% of capacitance retention at 10 A/g after 10000 cycles); besides, its power/energy density are 3694.084 W/kg and 26.289 Wh/kg, respectively. Therefore, the combination of facile synthesis strategy and excellent electrochemical performance makes Eleocharis dulcis-derived porous carbon as a promising electrode material for supercapacitor.